Analysis of Migrant Teachers' Life Experiences in Early Childhood Education in Canada - Ncube, Gugulethu; Ajani, Oluwatoyin Ayodele (EDUCARE: Journal of Primary Education, 2024)
This study explores the lived experiences of migrant early childhood education (ECE) teachers in Canada, emphasizing their contributions to cultural and linguistic diversity as well as the challenges they face in professional integration. With Canada’s diverse population and increasing number of migrant educators, understanding their experiences is essential to support inclusive educational practices. The study investigates how migrant ECE teachers contribute to multiculturalism and multilingualism in classrooms, enhancing children's social, cognitive, and cultural development. Despite these positive impacts, migrant teachers encounter obstacles such as credential recognition, language barriers, and systemic biases, which hinder their professional integration and potential contributions. Utilizing qualitative methodology, semi-structured interviews were conducted with nine migrant educators representing diverse cultural backgrounds. The findings of this study suggest that systemic barriers hinder the full integration of migrant educators into Canada’s early childhood education (ECE) system despite their significant contributions to cultural and linguistic diversity. Better recognition of their credentials, increased professional support, and more inclusive policies are needed to maximize their potential and reflect their experiences well in Canada’s ECE system. The contribution of this study is to identify and highlight systemic barriers that hinder the full integration of migrant educators into the Early Childhood Education (ECE) system in Canada. The findings call for better credential recognition, increased professional support, and more inclusive policies to maximize the potential of migrant educators and ensure their experiences are well reflected in the Canadian ECE system. This study contributes to proposing changes that can help address these inequities and increase diversity and inclusion in early childhood education in Canada.